Effects of a Cardiac Rehabilitation Program Versus Usual Care on Cardiopulmonary Function in Patients With Cardiac Syndrome X. Issue 1 (January 2020) - Rahmani, Reza; Niyazi, Sepideh; Sobh-Rakhshankhah, Amir; Guazzi, Marco; Mazaheri, Reza; Hashemi, Naeimeh; Khoddami-Vishteh, Hamid-Reza
Abstract : Purpose: Because of uncertainty in the pathophysiological process, the treatment of cardiac syndrome X (CSX) is still under study. Addressing the effects of cardiac rehabilitation (CR) can help promote the prescription of this modality as an adjuvant therapy for these patients. Methods: This study was performed on 30 patients with effort-induced angina pectoris using a positive exercise test and/or myocardial perfusion scan in the absence of obvious stenosis or a stenosis of <50% on coronary angiography. The patients were divided into the CR and usual care (UC) groups and underwent cardiopulmonary exercise testing with gas exchange analysis before and after the study. The Duke Treadmill Score was used to compare prognosis and survival estimates of patients. Results: An increase in peak oxygen uptake ( O2 ) was significantly higher in the CR group than in the control group ( P = .017). Resting O2 was also increased in the CR group, but its difference with the UC group was not statistically significant. Resting O2 pulse was increased in the CR group, which significantly differed between groups ( P = .041). Exercise test duration and the Duke Treadmill Score significantly increased in the CR group as compared with the UC group ( P = .003 and P = .002, respectively). Also, recovery heart rate in the first minute was significantly improved in CR group. Conclusion: Adding a 4-wk course of CR to UC for patients with CSX not only increased the Duke Treadmill Score and exercise test duration but also improved the resting O2 pulse, peak O2, and first-minute recovery heart rate. Abstract : The findings showed that adding a 4-wk course of cardiac rehabilitation to usual care for patients with cardiac syndrome X not only increased the Duke Treadmill Score and exercise test duration but also improved the resting oxygen (O2 ) pulse, the peak O2 uptake, and the first-minute recovery heart rate.